Bodies of knowledge in ancient Mesopotamia : the diviners of late Bronze Age Emar and their table collection - Rutz, Matthew. (Ancient Magic and Divination, 2013)
In Bodies of Knowledge in Ancient Mesopotamia Matthew Rutz explores the relationship between ancient collections of texts, commonly deemed libraries and archives, and the modern interpretation of titles like 'diviner'. By looking at cuneiform tablets as artifacts with archaeological contexts, this work probes the modern analytical categories used to study ancient diviners and investigates the transmission of Babylonian/Assyrian scholarship in Syria. During the Late Bronze Age diviners acted as high-ranking scribes and cultic functionaries in Emar, a town on the Syrian Euphrates (ca. 1375-1175 BCE). This book's centerpiece is an extensive analytical catalogue of the excavated tablet collection of one family of diviners. Over seventy-five fragments are identified for the first time, along with many proposed joins between fragments.